0224 Experimental Sleep Restriction Increases Somatic Complaints in Healthy Teens. (12th April 2019) - Krietsch, Kendra N; King, Chris; Beebe, Dean W
Abstract: Introduction: Both sleep disturbance and somatic symptoms (bodily complaints like aches/pains, fatigue, or GI distress) are common in adolescent medical and psychiatric populations. Although sleep and somatic complaints to some degree may reflect a 'primary' medical or mood disorder, there is evidence in adults that short sleep alone can contribute to such symptoms. This study tested the effect of experimentally restricting sleep duration on self-reported somatic symptoms in a medically and psychologically healthy teen sample. Methods: N=22 teens (ages 14-18) completed a 3-week, within-subject counterbalanced sleep restriction-extension experiment. Following a 7-day sleep stabilization week, teens were randomly assigned to 5 nights of either Short Sleep (6.5 hrs/night in bed) or Healthy Sleep (9.5 hrs/night in bed). Teens completed measures of number of somatic complaints (Pain and Symptom Assessment Questionnaire - PSAQ) and degree to which these symptoms are bothersome (Children's Somatization Inventory - CSI) the morning after completing each condition. Following a 2-night washout period, teens crossed over to complete the alternate 5-night sleep condition and then repeated the PSAQ and CSI. Adherence to experimental condition was confirmed via actigraphy. Results: Compared to the Healthy Sleep condition, teens averaged 125 minutes less nightly sleep in the Short Sleep condition. They reported significantly more somatic symptoms based on total PSAQ scores during Short Sleep (p=.01, d=.55), and a moderately large effect (although not statistically significant) persisted even after excluding the fatigue sub-scale (p=.127, d=.32) to conservatively remove items more manifestly related to sleep. Teens also reported being significantly more bothered by somatic symptoms during the Short Sleep condition based on total CSI scores (p=.005, d=.60), which does not include sleep or fatigue items. Conclusion: Among a small but healthy teen population, restricting sleep opportunity to 6.5hrs/night (an amount not unrealistic for many teens) led to causal increases in self-reported somatic symptoms. Findings point to the importance of addressing sleep complaints in adolescent populations currently experiencing or vulnerable to developing somatic symptoms. Support (If Any): R01 HL120879